Koping Religius pada Kelompok Penderita HIV/AIDS - Muhammad Bagus Andrianto; Asih Dewi Setyawati; Muhammad Muin; Fery Agusman Motuho Mendrofa (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study was to see a picture of people living with religious HIV / AIDS. The method in this research is using descriptive analysis. From a total of 69, the results of the study obtained moderate religious data on people living with HIV / AIDS of 42 respondents (60.9%). In conclusion, the need for support and guidance for HIV / AIDS in increasing adaptive coping can manage the disease it is experiencing. Keywords: HIV / AIDS, Religious Coping